2000
DOI: 10.1161/01.str.31.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Stroke in Relatives of Hypertensives

Abstract: Background and Purpose-The genetic basis of stroke is poorly understood. We evaluated patterns of familial aggregation of hypertension and stroke to test the hypothesis that inherited susceptibility to these disorders may be determined by a common set of factors. Methods-Genealogical and medical history information was obtained for a cohort of 354 hypertensive probands ascertained in a clinic-based setting, their 1427 first-degree relatives, and 239 of their spouses. Risks of stroke and hypertension in biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…The larger magnitude in the ORs for siblings than for parents (Table 2) may be due partly to this clustering effect. In fact, a previous clinic-based case-control study showed a higher observed risk in parents than in siblings of the probands, 8 a trend not consistent with out results. Another possibility is the effects related to the variability in age among parents and siblings: we previously found an aging-related decrease in the familial aggregation of both hypertension and stroke, and assumed that factors specific to individuals would have become more influential than shared familial factors in the development of the diseases at older ages.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The larger magnitude in the ORs for siblings than for parents (Table 2) may be due partly to this clustering effect. In fact, a previous clinic-based case-control study showed a higher observed risk in parents than in siblings of the probands, 8 a trend not consistent with out results. Another possibility is the effects related to the variability in age among parents and siblings: we previously found an aging-related decrease in the familial aggregation of both hypertension and stroke, and assumed that factors specific to individuals would have become more influential than shared familial factors in the development of the diseases at older ages.…”
Section: Discussioncontrasting
confidence: 81%
“…Additionally, a common genetic basis for hypertension and stroke might be affected through genes underlying the risk factors for these traits (eg, obesity, atherosclerosis, diabetes). 8 This study is subject to some limitations. Since our population was community-based, there was a possibility that some probands are sibs to other probands born to the same parents.…”
Section: Discussionmentioning
confidence: 95%
“…Many of the established and emerging risk factors described in the sections that follow, such as hypertension, diabetes, and hyperlipidemia, have both genetic and environmental/behavioral components. [45][46][47] Elevations of blood homocysteine occur with 1 Class I Conditions for which there is evidence for and/or general agreement that the procedure or treatment is useful and effective.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…This is consistent with previous general population studies that have shown that FHx Stroke is more common in hypertensive than normotensive subjects 17,18 and a previous case-control study in which stroke patients were more likely to have a FHx of hypertension than controls. 19 Given that hypertension has a major genetic component, 12 heritability of stroke may partly be conferred by an inherited tendency for hypertension.…”
Section: Discussionmentioning
confidence: 99%